Seventh Five Year Plan 1985-90 - Planning Commission (Planning Commission, 1985)
In the first two years of the plan the pace of public investment has been maintained at the required level. Infrastructural constraints have been lightened and industrial growth has been sustained at unprecedently high levels for three years running. Anti-poverty and employment programmes have been generally strengthened and human resource development has been given new direction with the new National Policy on Education. 1.2 In this, the third year of the Plan many parts of the country are experiencing a drought of exceptional severity. In others floods have caused severe damage. The underlying strength and resilience of the economy, the policy making apparatus and development administration have together made it possible to cope with these natural disasters without disrupting the development process. Speedy and effective measures have been taken to provide relief, organise food supplies and contain inflationary pressures in critical markets. The infrastructural sectors have risen to the challenge posed by the reduced availability of hydel energy and heavier demands for transportation. Industrial growth in the first part of the year has been at an exceptionally high level.
Mid Term Appraisal Government of India Planning Commission